2021
DOI: 10.2478/candc-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Using the FITradeoff method to solve a shopping mall location problem in the northeastern countryside of Brazil

Abstract: This paper presents a practical case involving a shopping mall location problem in the northeast countryside of Brazil. In this problem, conflicting objectives have been expressed in terms of seven criteria. Then, ten cities of the northeastern countryside have been selected to compose the space of actions. The problem plays a special role since Brazil is a big country that requires investments in the countryside. Thus, the shopping mall aims to stimulate economic growth in the respective region. In the study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…This, exactly, is the situation with the study and data reported in Sousa Ribeiro et al (2021). Side by side with effective performance of the procedure, a set of data is obtained, which also has a definite value in itself.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…This, exactly, is the situation with the study and data reported in Sousa Ribeiro et al (2021). Side by side with effective performance of the procedure, a set of data is obtained, which also has a definite value in itself.…”
Section: Introductionsupporting
confidence: 56%
“…
Taking as an example the very interesting and motivating paper by Sousa Ribeiro et al (2021) an attempt is made of providing a couple of insights into the decision making process from the point of view of the potentially helpful aspects of data analysis and OR-related modelling. These are just hints and suggestions, meant primarily to emphasise the multifaceted character of the decision making situations and processes, especially when concerning more complex issues.
…”
mentioning
confidence: 99%